Plasma 1, 25-Dihydroxyvitamin D and the Risk of Developing Hypertension: The Prevention of Renal and Vascular End-Stage Disease Study. Issue 3 (September 2015) - van Ballegooijen, Adriana J.; Gansevoort, Ron T.; Lambers-Heerspink, Hiddo J.; de Zeeuw, Dick; Visser, Marjolein; Brouwer, Ingeborg A.; Kema, Ido P.; de Borst, Martin H.; Bakker, Stephan J.L.; Joosten, Michel M.
Abstract : Previous observational studies on the vascular effects of vitamin D have predominantly relied on measurement of its inactive precursor, 25-hydroxyvitamin D, whereas the active metabolite 1, 25-dihydroxyvitamin D may be of more physiological relevance. We prospectively studied the associations of 1, 25-dihydroxyvitamin D and 25-hydroxyvitamin D with hypertension risk (blood pressure ≥140/90 mm Hg or initiation of blood pressure–lowering drugs) in 5066 participants aged 28 to 75 years, free of hypertension at baseline from the Prevention of Renal and Vascular End-Stage Disease Study, a well-defined cohort with serial follow-up. We measured plasma 1, 25-dihydroxyvitamin D and 25-hydroxyvitamin D using liquid chromatography-tandem mass spectrometry. Mean±SD plasma concentration of 1, 25-dihydroxyvitamin D was 145±47.0 pmol/L and 25-hydroxyvitamin D was 58.6±23.8 nmol/L. During a median follow-up of 6.4 years, 1036 participants (20.5%) developed hypertension. As expected, low 25-hydroxyvitamin D was associated with a higher hypertension risk; each 1-SD decrement in 25-hydroxyvitamin D was associated with a 8% higher hypertension risk (hazard ratio, 1.08; 95% confidence interval, 1.01–1.16) after adjustment for potential confounders. However, the association of 1, 25-dihydroxyvitamin D was in the opposite direction; each 1-SD decrement of 1, 25-dihydroxyvitamin D was associated with a 10% lower hypertension risk (hazard ratio, 0.90; 95% confidence interval, 0.84–0.96), independent of potential confounders. In contrast to the inverse association between 25-hydroxyvitamin D and hypertension risk, 1, 25-dihydroxyvitamin D was positively associated with risk of hypertension. Thus, higher circulating concentrations of 1, 25-dihydroxyvitamin D are associated with a higher risk of hypertension.